The emergence of modern Southeast Asia a new history - Owen, Norman G.; Chandler, David; Roff, William R.; Steinberg, David Joel; Taylor, Jean Gelman; Taylor, Robert H.; Woodside, Alexander; Wyatt, David K. (University of Hawaiʻi Press, 2005)
The Emergence of Modern Southeast Asia offers a new and up-to-date perspective on this complex region. Although it does not neglect nation-building (the central theme of its popular and long-lived predecessor, In Search of Southeast Asia), the present work focuses on economic and social history, gender, and ecology. It describes the long-term impact of global forces on the region and traces the spread and interplay of capitalism, nationalism, and socialism. It acknowledges that modernization has produced substantial gains in such areas as life expectancy and education but has also spread dislocation and misery.